FENOMENA PEMUJAAN RATU NIANG DI KOTA DENPASAR - I Made Surawati; I Nyoman Putra Adnyan (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
Before the Hinduism began to influence the Balinese culture, the Balinese society had been applying symbols as one part of their ritual tradition. One of the symbols was in the form of feminine force. This has been applied as the symbol of fertility which has been traditionally handed down. In the city of Denpasar, there is similar tradition, in which the feminine force is manifested under the believe that the citizen would be bestowed with successful supports, especially for those who have business occupation. The manifestation is in the form of Ratu Niang, as the representation of the Almighty God. In this man- ifestation, God is belived to bless the community to successfully improve their prosperity and welfare. In Denpasar, there are several sites of this Ratu Niang worship, the unique one is located at Prima Me- dika Hospital, on the South part of Jero Kuta and the biggest one is at Pura Geria Anyar Tanah Kilap